2012
DOI: 10.1007/978-3-642-35311-6_38
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Best-Response Dynamics in Games with Conflicting Congestion Effects

Abstract: Abstract. We study the model of resource allocation games with conflicting congestion effects that was introduced by Feldman and Tamir (2012). In this model, an agent's cost consists of its resource's load (which increases with congestion) and its share in the resource's activation cost (which decreases with congestion). The current work studies the convergence rate of best-response dynamics (BRD) in the case of homogeneous agents. Even within this simple setting, interesting phenomena arise. We show that, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We will refer to that model in this work. [22] showed that using the Max-Cost deviator rule, tightly bounds the convergence rate to 1.5n (worst-case) in these games. The Max-Cost deviator rule was also considered in [30] for Swap-Games [4].…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…We will refer to that model in this work. [22] showed that using the Max-Cost deviator rule, tightly bounds the convergence rate to 1.5n (worst-case) in these games. The Max-Cost deviator rule was also considered in [30] for Swap-Games [4].…”
Section: Related Workmentioning
confidence: 98%
“…x . As [22] showed, the cost function exhibits the following structure. Denote by l * the load minimizing the players' cost.…”
Section: Job Scheduling Games With Conflicting Congestions Effectsmentioning
confidence: 99%
“…Simultaneous updating by all players at each time step is studied in Quint et al (1997) for 2-player games and in Kash et al (2011) for anonymous games. Feldman and Tamir (2012) study the case in which the sequence of play depends on current payoffs. Feldman et al (2017) study the dynamic inefficiency of the best-response dynamic under different playing sequences.…”
Section: Introductionmentioning
confidence: 99%